Similarly:

So when we plug and into the left-hand side of , we get -- which means that they satisfy the equation. So we can call them solutions.Does that make sense?

]]>10. Work backwards to write a quadratic equation that will have solutions of x = 3 and x = -7.

Remember that here we wanted a quadratic equation with factors (x - 3) and (x + 7), because those equal zero when x = 3 and x = -7, respectively.

So a quadratic equation that has solutions x = 3 and x = -7 is (x - 3)(x + 7) = 0.

This time, you're given the quadratic equation (t - 8)(t + 3) = 0.

This has factors (t - 8) and (t + 3).

Can you see which values of t will make those equal zero?

]]>-They multiply to make .

For instance, -6 and 1 add to make -5, but their product is -6, so that doesn't work.

However, -8 and 3 add to make -5, and their product is -24, so that's the correct combination. Thus, we can factor like this:

Are you able to solve the question from here?

]]>Can you solve this by factoring?

]]>